Psychopathology among individuals seeking minimally invasive cosmetic procedures. (14th August 2019) - Özkur, Ezgi; Kıvanç Altunay, İlknur and Aydın, Çiğdem
Abstract: Objectives: In recent years, so many people want to alter their physical appearance with the purpose of raising their social and psychological well‐being and the demand for minimally invasive cosmetic procedures (MICPs) has continued to rise. Our study aims to investigate the psychological profile of people seeking cosmetic procedures. Study Design: The present observational cross‐sectional study was conducted with a sample of 54 participants seeking cosmetic procedures (botulinum toxin injections, soft tissue filler injection, mesotherapy, platelet‐rich plasma, and dermaroller treatments). Those patients were compared to the control group, who did not have any kind of cosmetic procedure (including cosmetic surgery) before and who did not want to have any of these procedures. Methods: The research volunteers were invited to complete the demographic questionnaire (e.g., age, gender and history of procedures) as well as psychological scales. Psychological scales includes the validated and reliable The Brief Symptom Inventory (BSI), Automatic Thoughts Scale (ATS), and Social Adaptation Self‐Evaluation Scale (SASS). Results: Users of MICP were mostly female (n = 46, 85%) and had some high school education or higher and showed higher scores on General Severity Index ( P = .013), anxiety ( P = .018), depression ( P = .004), interpersonal sensitivity ( P = .008) of BSI and also higher on ATS ( P = .022) and lower on SASS ( P = .001) scores that mean less social adaptation. There was a statistically positive correlation between age and GSI, anxiety, depression, interpersonal sensitivity, somatization scores of BSI, and negative correlations between SASS scores and age and number of past procedures. Conclusion: Our study findings highlight the importance of understanding individuals' psychological symptoms who are seeking cosmetic procedures.